KECERDASAN0INTELEKTUAL, 0KECERDASAN0EMOSIONAL0DAN KECERDASAN0SPIRITUAL0PENGARUHNYA0TERHADAP0KINERJA KARYAWAN (Pada Karyawan0PG0Kebon0Agung Malang) - M Rihal Irsyada; Hadi Sunaryo; A Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe research was0conducted0at0PG Kebon0Agung Malang, East Java. The purpose of this research is to examine and analyze the effect of intellectual quotient, emotional intelligence and spiritual intelligence on employee performance.The variables used are intellectual0quotient, 0emotional0intelligence0and0spiritual intelligence0as0independent0variables, 0employee0performance as the0dependent variable. The sample used was 88 PG employees of the Agung Malang garden in East Java using the proportional stratified random method. Data collection method used is questionnaire. The analysis used includes instrument testing, classical assumption test, normality test, linear regression multiple regression, hypothesis testing and determination coefficient test using multiple linear regression analysis with the help of SPSS 14.0 for Windows software.The results showed0that intellectual0quotient, 0emotional intelligence, and spiritual intelligence had a significant effect on the employees performance of the Malang Kebon Agung PG in East Java.Keywords : Intellectual Quotient, Emotional Intelligence, Spiritual Intelligence and Employee Performance